Tumor budding is a prognostic marker for overall survival and not for lymph node metastasis in Oral Squamous Cell Carcinoma - Systematic Review Update and Meta-Analysis - Gouri S. Panchannavar; Punnya V. Angadi (Elsevier, 2024)
Objective: Tumor budding (TB) has shown promising results as a prognostic marker in several cancers such as colorectal carcinoma, breast carcinoma etc. It has been co-related to aggressiveness of the tumor and can also predict the metastasis to the lymph nodes. This systematic review evaluates the prognostic potential of TB in predicting lymph node metastasis (LNM) in OSCC. Data sources: Systematic search was carried out in the electronic data-bases i.e. PubMed, Cochrane and Google scholar for original studies related to TB in OSCC. The assessment of risk bias was done using QUIPS tool. Meta-analysis was done using STATA software. Results: A total of 25 articles were included. A significant association was noted for overall survival and prognosis but not for TB LNM in OSCC. Meta-analysis revealed a pooled estimate i.e odds ratio of 2.10 (CI - 0.00 - 4.20) for TB and LNM while for overall survival, it was 2.29 (CI-1.81-2.76). Conclusion: Tumor budding though is strongly associated with LNM in OSCC did not show significant relationship in this systematic review but demonstrated a higher correlation with overall survival. It highlights that TB is an important parameter for prognosis of oral cancer but its potential in prediction of LNM needs further validation.